2021
DOI: 10.1097/mph.0000000000002131
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma With Opsoclonus-Myoclonus-Ataxia Syndrome: Role of Chemotherapy in the Management: Experience From a Tertiary Care Center in a Resource-limited Setting

Abstract: Children with neuroblastoma (NB) and opsoclonus-myoclonus-ataxia syndrome (OMAS) have a favorable oncologic outcome and overall survival. In contrast, despite intensive multidrug immunomodulation, the neurologic outcome is complicated by the relapsing nature of the neurologic symptoms and long-term neurobehavioral sequelae. Being associated with low-risk NB, there exists an ambiguity in the current literature regarding the administration of chemotherapy in these children. We reviewed our archives for children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Speech and behavioral problems are especially detected. [19][20][21][22] The rate of neurological sequelae, including the persistence of OMAS symptoms, was reported as 56.5% in one study, while in another, it was reported between 20 and 60%. 13,22 In our study, the rate of sequelae is 33%.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Speech and behavioral problems are especially detected. [19][20][21][22] The rate of neurological sequelae, including the persistence of OMAS symptoms, was reported as 56.5% in one study, while in another, it was reported between 20 and 60%. 13,22 In our study, the rate of sequelae is 33%.…”
Section: Discussionmentioning
confidence: 89%
“…However, as seen in the literature, the administration of chemotherapy is beneficial in selected cases in terms of intensifying possible immunosuppression and preventing long-term sequelae. 8,18,19 In our center, an institutional chemotherapy scheme consisting of six cycles of cisplatin, cyclophosphamide, and vincristine was applied to patients who could undergo subtotal tumor excision or were diagnosed with tru-cut biopsy or could not be obtained a definitive MYCN result (►Table 2). We consider that tumor or OMAS recurrences will be less after chemotherapy in such cases, and further studies are needed on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…16 17 Interestingly, Anand et al found chemotherapy administration (cyclophosphamide being a part of the regime) as the only variable significantly predicting a favorable neurologic outcome in neuroblastoma-OMAS. 14…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis, prompt removal of underlying tumor, aggressive immunomodulation, and regular follow-up for relapses have been found to reduce morbidity. 6 7 8 9 10 14 However, delayed diagnosis and neurobehavioral sequalae are common. 5 6 7 10 Misdiagnosis as cerebellar ataxia, delayed detection, and removal of neurogenic tumors and immunomodulatory treatments have all been reported to affect outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation